Quality management in civil construction: Analysis of the Brazilian Program of Quality and Productivity in Habitat in Juazeiro do Norte, Ceará (Research, Society and Development, 2020)
In the construction sector, as well as in other economic activities, in recent years the interest in obtaining quality certifications has increased, in which the interest in improving processes related to quality and productivity is proving increasingly competitive. In this sense, the present work aims to analyze the Brazilian Program of Quality and Productivity in Habitat in construction companies in Juazeiro do Norte, Ceará. This study aims to present its motivations, characteristics and importance in the current scenario of civil construction. A survey was carried out in the database of the program's website, first in the state of Ceará and then with greater emphasis on the city of Juazeiro do Norte. Based on all research on quality and the program, a questionnaire was prepared that was answered by employees of four construction companies that operate in the city. The companies that participated in the study are at level A certification and operate in the construction sector with residential constructions. Based on the data collected, the motivations and difficulties for implementing the system were identified. It was found that the main reasons that led companies to join the PBQP-h were the increase in quality and the need for certification to obtain financing. Regarding the difficulties pointed out by the companies, it is possible to highlight the preparation of documents, adequacy of standards and training, since there is resistance on the part of the workers in the acceptance of the changes. With this 100% of the companies surveyed chose to hire external consulting to streamline the certification process.